Insecticide susceptibility of the green rice leafhopper, Nephotettix cincticeps Uhler - MORIYA, Shigeo; MAEDA, Yoichi (Kyushu Plant Protection Research, 1972)
The susceptibility to 7 carbamate insecticides of the green rice leafhopper, collected from several points in Kyushu district in 1971, was determined by means of microtopical application method. The LD50 values of each insecticide to the leafhopper tested were few times higher than those to the susceptible strain. A little local fluctuation was observed on the susceptibility among collect areas except Kumamoto, where the leafhopper showed rather low susceptibility to any test insecticides. During recent ten years, LD50 values of carbaryl and malathion to the leafhopper at Chikugo increased to about 9 times compared with initial values. It is considered that susceptibility of the leafhopper to other substituted phenyl carbamate insecticides also has generally decreased in Kvushu district.